Karakterisasi Tiga Tumbuhan Obat Antihiperkolesterolemia dengan Pendekatan Berbasis Profil Anatomi, Histokimia, dan Fitokimia - Reny Syahruni; Abdul Halim Umar; Nur Hidayah Asnar (Pharmacon: Jurnal Farmasi Indonesia, 2022)
It is very important to validate the characterization of medicinal plants to ensure their use, especially if the medicinal plants are to be used only for certain organs. This study aimed to obtain information related to the type of secretory structure and the secondary metabolites they accumulated, as well as the phytochemical profile of three antihypercholesterolemic plants. This study used three organs (leaves, stem bark, and roots) from Moringa oleifera, Muntingia calabura, and Annona muricata with anatomical, histochemical, and phytochemical methods. Anatomical and histochemical tests were carried out by observing the fresh sample incision to see the presence of secretory structures (secretory cavities, glandular trichomes, idioblast cells). Histochemical tests were carried out on fresh sample incision using specific reagents to determine the secretory structure producing/accumulating secondary metabolites (alkaloids, phenolics, lipophilic, and terpenoids), while phytochemical tests were carried out to identify their secondary metabolites with thin layer chromatographic technique (qualitative). The results showed that the three antihypercholesterolemic plants contained several secretory structures, namely: glandular trichomes, idioblast cells, and secretory cavities, and were identified as containing secondary metabolites of alkaloids, phenolics, lipophilic, and terpenoids. This finding is supported by the chromatographic results of the extracts of the three species. Techniques based on anatomical, histochemical, and phytochemical profiles can be applied to identify plant organs containing specific secondary metabolites